Morphological comparison of Alosa shad species using morphometric and meristic characteristics in the southern coast of Caspian Sea - Seyed Ramin Ghotbi Jokandan (Taxonomy and Biosystematics Journal, 2015)
Comparative morphological study carried out for four shad species of the genus Alosa including A. braschnikowi, A. caspia, A. kessleri and A. saposchnikowii in the southern coast of Caspian Sea. Totally 239 specimens were collected from autumn 2013 to spring 2014 in three beaches in fisheries stations (Anzali Port, Noor-Mahmoudabad, Gorgan Bay) along the southern coast of the Caspian Sea. Nine meristic and twenty five morphometric characteristics were used for morphological comparison. The Results of One-Way ANOVA, Principle component Analaysis (PCA) and Descriminant Function Analysis implies efficeny of selected morphological characteristics for the separation of these species. Although no diagnostic characteristics were identified but morphometric characters showed higher variation within four species. In addition to previous known key characters which were associated with the size and number of gill rackers and filaments on first branchial arc, here some other key characteristics incuding Dorsal and Anal fin’s hight, Head’s height, width and length, Snout’s length, Caudal peduncle’s height, Post Orbital’s lenght, Ventral and Pectoral fin’s length in morphometrics and Number of Caudal fin rays, Number of hard and soft dorsal fin rays in meristics were significantly different (p<0.05) in comaprison within four shad species. Although overlaps were appeared in comparison of all measured morphometrics and counted meristic chatracteristics range but mentioned characteristics could be useful in better and more accurate identification of these four Alosa shad species along the southern coast of Caspian Sea.